Pottery and Burial Customs in Hellenistic Megara, Greece - Chairetakis, Yannis (Journal of Hellenistic Pottery and Material Culture, 2021)
The city of Megara is located on a particularly strategic site with the advantages of being in close proximity to the Saronic Gulf and having fertile farming land (fig. 1). During the 7th and 6th centuries BCE the town was situated on the two low fortified hills of Alkathos and Karia, which were surrounded by the cemeteries. The erection of the fortification wall in the period between 479 to 460 BCE resulted in the relocation of the cemeteries outside the boundaries of the fortified town, and also at a distance from the banks of the two streams, Mauratza and Exobrisis, which functioned as ditches for the wall (fig. 2). Tombs of classical and Hellenistic times were located near the main roads, leading to Megaris and the neighbouring cities (Corinth, Athens, Thebes). Besides, Pausanias (1, 43, 3–5; 1, 44, 3; 1, 44, 6) describes special burials of mythical persons and heroes inside and outside the city. The habit of the Megarians to build public buildings around the tombs of heroes is also interesting, because they thought that these graves could protect public life and political assemblies. The Megarians, after all, had distinctive beliefs about death, and Cynic Diogenes observes that they »feast as if to die tomorrow, and build as if they were never to die at all«.